The Assessment of Technical Efficiency in Public Employment Services (Economic and Political Thought, 2018)
The authors propose a method of assessment of efficiency of regionalPES’s by selecting statistically significant inputs and outputs as well as theenvironmental variable. In the final DEA model variables which show thepositive correlation and statistically significant relationships between inputvariables and outputs (effects) were selected. Among the environmentalvariables the one with the strongest relationships with output variableswas chosen. For the purposes of the resource management assessment ofPES’s an analysis of technical relative efficiency of two Polish provinces wasconducted using the Data Envelopment Analysis (DEA) method. Theseprovinces represent a different labour market situation as Podlaskie is one ofthe peripheral regions and Mazowieckie voivodeship has the best economicindicators in Poland. The analysis has shown that the environmental variablehas a significant impact on PES performance (overall improvement in technicalefficiency results). The results of the analysis also enabled the identificationof benchmark PES’s, the identification of areas requiring improvement andthe selection of changes that will contribute to improving efficiency moreprominently than for other variables.
Keywords: DEA; technical efficiency; public employment services; labour market policy